2021
DOI: 10.3390/life11111166
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C Intervention for Critical COVID-19: A Pragmatic Review of the Current Level of Evidence

Abstract: Severe respiratory infections are characterized by elevated inflammation and generation of reactive oxygen species (ROS) which may lead to a decrease in antioxidants such as vitamin C and a higher requirement for the vitamin. Administration of intravenous vitamin C to patients with pneumonia and sepsis appears to decrease the severity of the disease and potentially improve survival rate. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection causes pneumonia, sepsis and acute respiratory distre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 62 publications
2
16
0
2
Order By: Relevance
“…The latter review, albeit detailed, lacked a metaanalytic approach (34). Taken together, our and previous (33,34) contributions may provide the readers with the whole picture of the potential role of vitamin C in patients with COVID-19.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The latter review, albeit detailed, lacked a metaanalytic approach (34). Taken together, our and previous (33,34) contributions may provide the readers with the whole picture of the potential role of vitamin C in patients with COVID-19.…”
Section: Discussionmentioning
confidence: 89%
“…On the other hand, the authors of another recent relevant pragmatic review of the literature concluded that "intravenous vitamin C intervention may improve oxygenation parameters and reduce inflammatory markers" (34). The latter review, albeit detailed, lacked a metaanalytic approach (34). Taken together, our and previous (33,34) contributions may provide the readers with the whole picture of the potential role of vitamin C in patients with COVID-19.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In the New Zealand context, Māori and Pasifika peoples are at increased risk for all of these risk factors [ 50 ], as well as for morbidity and mortality from severe COVID-19 [ 51 , 52 ]. It is interesting to note that these risk factors also contribute to hypovitaminosis C [ 28 ], as does COVID-19 itself [ 53 ]. Due to vitamin C’s well-known immune supportive roles [ 54 ], future research restoring adequate vitamin C status in people with hypovitaminosis C and infection risk factors, and exploring its effects on infection susceptibility and severity appear warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Severe COVID-19 is characterised by the complications of pneumonia, acute respiratory distress syndrome (ARDS) and sepsis, typically requiring hospitalisation and intensive care for respiratory support [ 36 ]. Patients with pneumonia, ARDS and sepsis generally have severely depleted vitamin C levels [ 9 ]; comparable findings have been reported with COVID-19 patients [ 37 ]. Vitamin C supplementation of hospitalised patients with pneumonia has indicated decreased respiratory symptoms in the most severely ill and a dose-dependent decrease in the duration of hospital stay [ 29 ].…”
Section: Adjunctive Therapy For Severe Diseasementioning
confidence: 55%